Ramana Maharshi - Swaminathan, K. (New Delhi : National Book Trust, India : distributors, Thomson Press (India), 1975)
On the life and teachings of Ramana Maharshi, 1879-1950, seer, philosopher of South India.
Bibliography: p. [153]-156.
Keywords: Ramana, -- Maharshi